Integration of Healthcare in Belgium: Insufficient, but There Is Hope; Comment on "Integration or Fragmentation of Health Care? Examining Policies and Politics in a Belgian Case Study" - Jan De Lepeleire (Kerman University of Medical Sciences, 2023)
The maturity of integrated care in Belgium is rather low. The reasons are the country's complex organization, a lack of leadership and finances, an abundance of pilot projects, very long implementation and change processes, a healthcare system driven by providers and different cultures of action. However, new projects and ongoing research can help overcome these barriers. The primary care zones in Flanders, the National Hospital Plan and the Federal Plan to support mental health in particular are luxating opportunities. Well planned research is urgently needed to confirm the hope these projects arouse.